A Comparison of the Pāli and Chinese Versions of the Brahma Saṃyutta, a Collection of Early Buddhist Discourses on Brahmās, the Exalted Gods. (15th January 2015) - Choong, Mun-Keat
Abstract : Saṃyutta of the Pāli Saṃyutta-nikāya in conjunction with two other versions preserved in Chinese translation in Taishō vol. 2, nos 99 and 100. Then it compares the main teachings contained in the three versions. This comparative study of these three different versions focuses on some shared images of Brahmās and on disagreements of some teachings presented in the three versions. It reveals similarities and significant differences in structure and doctrinal content, thus advancing the historical/critical study of early Buddhist doctrine in this area.